Unmanned Aerial Vehicle Path Planning Using Water Strider Algorithm - Sampath, Madhusudhanan; Duraisamy, Abitha Kumari; Samuel, Amalorpava Mary Rajee; Manickam Malu, Yamuna Devi; M, Nirmala (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
This paper presents a multi-agent optimal path planning and obstacle avoidance using a water strider algorithm (WSA) based on Sequential Convex Programming (SCP). The outcome is to find optimal collision-free trajectories. The best collision-free trajectories with minimum control effect is needed in the multi-agent route planning technique, which makes use of a centralized WSA algorithm that can guide drones over congested environments while avoiding both static and moving objects. By applying convex constraints on the drones’ such as acceleration, velocity input and jerk, the feasibility of the trajectory is ensured. The optimal trajectory path is iteratively created using SCP and followed by WSA. The outcome guarantees the correctness of the linearization. Since the optimization is centralized, it is possible to find a feasible collision-free path, and the results are validated pre-determined formation. It is shown that the WSA algorithm scales with O3(n), where n is the number of drones.